RESIDENTIAL TRANSACTIONS AS LEADING ECONOMIC INDICATOR (Globalization and Business, 2023)
It is important to predict trends of economic develop- ment for any country. Researchers and practitioners use dif- ferent ways for evaluation and forecasting economic activity. Identification of indicators, which change impact on the econ- omy in general, is one of the widespread methods. The most appropriate tools to solve this problem are the leading indica- tors and indexes based on leading indicators. The selection of indicators depends on the specificity of the country’s econo- my. Among the leading economic indicators is the dynamics of applications for the Building permissions for private hous- es, and can also be successfully use residential transactions. Depending on the above, the paper deals the aspects of cal- culation of leading economic indicators. This paper analyses some aspects of the effectiveness of indicator for predicting economic activity and describes the methodological issues forward leading indicators. Particular attention is paid to anal- ysis of residential transactions dynamics as a leading indicator as in theoretical as in practical terms. The article highlights the peculiarities of its implementation in Georgia.